Clinical validation of the self-reported Glasgow Antipsychotic Side-effect Scale using the clinician-rated UKU side-effect scale as gold standard reference. (August 2020) - Schouby Bock, Marlene; Nørgaard Van Achter, Oona; Dines, David; Simonsen Speed, Maria; Correll, Christoph U; Mors, Ole; Østergaard, Søren Dinesen; Kølbæk, Pernille
Background: Antipsychotics are key for the treatment of psychotic and several non-psychotic disorders. Unfortunately, antipsychotic medications are associated with side effects, which may reduce quality of life and treatment adherence. Therefore, regular screening of antipsychotic side effects is essential. The Glasgow Antipsychotic Side-effect Scale is a patient self-report scale developed for this purpose. However, the Glasgow Antipsychotic Side-effect Scale has only been validated against another self-report side effect measure, which is suboptimal. Objective: We aimed to validate the Glasgow Antipsychotic Side-effect Scale using the clinician-rated Udvalg for Kliniske Undersøgelser side-effect rating scale as the gold standard reference. Results: 81 antipsychotic-treated outpatients with schizophrenia-spectrum disorders (age = 42±13 years; males = 43%, schizophrenia = 77%, illness duration: median = 11 years) completed the Glasgow Antipsychotic Side-effect Scale and were subsequently scored on the Udvalg for Kliniske Undersøgelser by trained raters. Sensitivity, specificity, positive predictive value and negative predictive value were calculated for paired Glasgow Antipsychotic Side-effect Scale and Udvalg for Kliniske Undersøgelser items. Sensitivity of Glasgow Antipsychotic Side-effect Scale items ranged from 33–96%, with 19 (86%) having >75% sensitivity. Lowest sensitivity emerged for "nocturnal enuresis" (33%), "galactorrhea" (50%) and "hyperkinesia" 14–99%, with 14 items (64%) having >75% specificity, being lowest for "asthenia" (14%), "polyuria/polydipsia" (35%), "sedation" (41%), "akathisia" (53%), "dystonia" (65%), "hyperkinesia" (68%), "hypokinesia" (70%) and "accommodation" (70%). Positive predictive value ranged from 7–85%, with six items (27%) having a positive predictive value >75%. Negative predictive value ranged from 40–98%, with 21 items (95%) having a negative predictive value >75%. The mean time to complete the Glasgow Antipsychotic Side-effect Scale was 4±2 minutes. Conclusion: The Glasgow Antipsychotic Side-effect Scale demonstrated satisfactory validity as a self-rated tool for antipsychotic side effects and may aid measurement-based care and decision-making.